2008
DOI: 10.1016/j.jtcvs.2008.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic aspects of the atrioventricular junction influencing radiofrequency Cox maze IV procedures

Abstract: Bipolar radiofrequency clamps are not sufficient to complete a Cox maze IV procedure. Moreover, they may compromise coronary arteries in patients with left coronary dominance. Lines to the atrioventricular annuli need to be completed with the cut-and-sew technique or with alternative monopolar energy devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Surgical technique and the efficacy of electrophysiology in performing mitral line with bipolar clamp alone has been described by Benussi et al [19]. However, the work of Castellá et al [20] noted the anatomical impossibility of forming the line with a bipolar clamp. In our study, we strictly followed Benussi's technique.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical technique and the efficacy of electrophysiology in performing mitral line with bipolar clamp alone has been described by Benussi et al [19]. However, the work of Castellá et al [20] noted the anatomical impossibility of forming the line with a bipolar clamp. In our study, we strictly followed Benussi's technique.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ablation of the isthmus, Castella et al demonstrated that bipolar clamps were not sufficient to achieve complete ablation of the atrioventricular junction in an anatomical study. [21] They concluded that an additional monopolar ablation device or the cut-and-sew technique was required to complete the isthmus ablation. In our center, we only use bipolar RF without monopolar RF for the sake of economic costs.…”
Section: Discussionmentioning
confidence: 99%
“…An example is the lesion extending to the mitral annulus, that although technically challenging, successful creation is associated with a significant decrease in left sided atrial flutter. 73 As energy technology-cryoablation and RF-ablation-has allowed for quicker therapy and more minimally invasive approaches, various groups have advocated for intentional utilization of incomplete lesion sets to decrease CPB and cross-clamp times. As previously mentioned, pulmonary vein isolation (PVI) is essential as most of the AF foci are from PV origin; however, performing only the PVI lesion set has a lower incidence of SR at 2-year follow-up when compared with a more complete linear lesion set and omission of the mitral annular lesion is associated with increased rates of left side atrial flutter.…”
Section: Complications Of Surgical Management Of Af Incomplete Ablatimentioning
confidence: 99%
“…As previously mentioned, pulmonary vein isolation (PVI) is essential as most of the AF foci are from PV origin; however, performing only the PVI lesion set has a lower incidence of SR at 2-year follow-up when compared with a more complete linear lesion set and omission of the mitral annular lesion is associated with increased rates of left side atrial flutter. [73][74][75] Although omitting the right atrial lesion set has a reduced incidence of postoperative pacemaker dependence, there remains question as to the longevity of SR maintenance when compared with a complete biatrial lesion set as demonstrated. Barnett and Ad demonstrated this in a meta-analysis confirming biatrial lesion sets result in better control of late AF (87 vs. 73%, p ¼ 0.05) than those constrained to the LA.…”
Section: Complications Of Surgical Management Of Af Incomplete Ablatimentioning
confidence: 99%
See 1 more Smart Citation